EDU455 : Instructional technology / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course introduces students to the various computer applications software such as word processing, desktop publishing, web pages development, spreadsheet use, telecommunications and their uses in all areas of education. Students will finish the course with a complete understanding of computers, how to use computer applications, and how to access information on the World Wide Web as an integrated teaching and learning tool. Students will also be exposed to teaching and learning systems or tools, such as web-based teaching and learning tools and educational portals. This will assist them in understanding other alternatives of teaching and learning techniques that can be used in classrooms. Students are also given hands-on experience with each technique or application being explained and demonstrated via workshops in a computer laboratory.